The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1364/boe.4.002187
|View full text |Cite
|
Sign up to set email alerts
|

Label-free multi-photon imaging using a compact femtosecond fiber laser mode-locked by carbon nanotube saturable absorber

Abstract: Abstract:We demonstrate label-free multi-photon imaging of biological samples using a compact Er 3+ -doped femtosecond fiber laser mode-locked by a single-walled carbon nanotube (CNT). These compact and low cost lasers have been developed by various groups but they have not been exploited for multiphoton microscopy. Here, it is shown that various multiphoton imaging modalities (e.g. second harmonic generation (SHG), third harmonic generation (THG), two-photon excitation fluorescence (TPEF), and three-photon ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…The design of the microscope, and the experimental procedure have been reported previously. 21,22 The light source in the system is an amplified erbium-doped mode-locked fiber laser operating at a central wavelength of 1560 nm. The maximum average power of the laser is 60 mW with a repetition rate of 75 MHz and 228 fs pulse duration at the sample surface.…”
Section: -mentioning
confidence: 99%
“…The design of the microscope, and the experimental procedure have been reported previously. 21,22 The light source in the system is an amplified erbium-doped mode-locked fiber laser operating at a central wavelength of 1560 nm. The maximum average power of the laser is 60 mW with a repetition rate of 75 MHz and 228 fs pulse duration at the sample surface.…”
Section: -mentioning
confidence: 99%
“…Additionally, the laser used should be capable of performing MPM and OCM using the same optical system. It was previously demonstrated that OCM and MPM can be performed using a compact ultrafast femtosecond fiberbased supercontinuum source 5,6 . Using such supercontinuum sources is much more effective both in space and price, but presents a challenge to the dichroic coatings since the bands that should be reflected and transmitted are wider.…”
Section: Previous Designsmentioning
confidence: 99%
“…In order to visualize the difference in optical properties between transferred and directly grown graphene we employed nonlinear microscopy technique. We used a multiphoton femtosecond microscope [12][13][14] introduced schematically in Fig. 3.…”
Section: Sample Preparationmentioning
confidence: 99%